1969
DOI: 10.2172/4805752
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Chemistry of Nitric Acid Solutions.

Abstract: This report was prepared as an account of Government sponsored work. Neither the United States, nor the Commission, nor any person acting on behalf of the Commission: A. Makes any warranty or representation, expressed or implied, with respect to the accuracy, completeness, or usefulness of the information contained in this report, or that the use of any information, apparatus, method, or process disclosed in this report may not infringe privately owned rights; or B. Assumes any liabilities with respect to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…As previously observed in α self-radiolysis, the formation of nitrite in HNO 3 is proportional to the absorbed dose. Kazanjian et al 89 observed an increase of nitrite, that reaches a maximum concentration in γ radiolysis for HNO 3 solutions with concentrations lower than 1 mol dm −3 while at concentrations higher than 1 mol dm −3 , the nitrite increase is linear. The authors suggest that a similar maximum concentration of nitrites for higher doses and β and α radiation, is not excluded.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As previously observed in α self-radiolysis, the formation of nitrite in HNO 3 is proportional to the absorbed dose. Kazanjian et al 89 observed an increase of nitrite, that reaches a maximum concentration in γ radiolysis for HNO 3 solutions with concentrations lower than 1 mol dm −3 while at concentrations higher than 1 mol dm −3 , the nitrite increase is linear. The authors suggest that a similar maximum concentration of nitrites for higher doses and β and α radiation, is not excluded.…”
Section: Resultsmentioning
confidence: 99%
“…Nitrite ions are produced indirectly via attack on nitrate ions by the water radiolysis primary species (reactions (13)–(31) ) or directly by ionizing radiation (reaction (9) ). Kazanjian et al 2 showed that the formation of HNO 2 in HNO 3 in solutions of concentrations higher than 1 mol dm −3 is a result of both direct and indirect action of ionizing radiation; Balcerzyk et al 35 showed that even in HNO 3 solutions of concentrations of 1 mol dm −3 , the direct effects of ionizing radiation have a non-negligible contribution to the formation of nitrate radicals or ions, which in turn can lead to formation of nitrite. Considering the acidity of the investigated solution and following its p K a value: p K a (HNO 2 /NO 2 − ) = 3.24 at 25 °C, 66 nitrite ions exist as nitrous acid.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiolysis of nitric acid primarily leads to the formation of HNO 2 ( ref. 23 and 70 ) and H 2 O 2 ( ref. 70 ) whereas radiolysis of TBP and TPH can generate many different degradation products such as alkenes, carbonyl compounds (R–CO–R′, R–CO–H), carboxylic acids (R–COOH), alcohols (R–OH), nitro compounds (R–NO 2 ) 23 and phosphorus compounds such as HBDP, H 2 MBP, H 3 PO 4 , etc.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of nitric acid has also an impact on the yields of water radiolysis products especially (H 2 and H 2 O 2 ). Furthermore, nitrous acid (HNO 2 ), or its basic form, nitrite ion (NO 2 – ) are mainly formed under nitrate ion solutions radiolysis due to an interaction between the radicals formed by the radiolysis of water and those formed by the radiolysis of nitrate ions. The first step of nitrous acid production is the formation of radical intermediates in neutral (eq ) or acidic media (eq ). …”
Section: Introductionmentioning
confidence: 99%